Drainage - Marshall, Duncan; Brown, Stephen; University of the West of England, Bristol. Faculty of the Built Environment (Bristol : Faculty of the Built Environment, University of the West of England, 2004)
This film briefly summarises the evolution and current practice of drainage in the UK. The first part of the film highlights using a variety of contemporary images, texts and photographs, the problems of disease and insanitary conditions in Victorian Britain. The main body of the film explains modern drainage practice, both above and below ground, and includes details on, problems of siphonage and the use of traps, two pipe and single stack systems, combined and seperate drainage systems, Modern pipework and fittings, trenches and pipe protection, inspection chambers, building regulations. The final part briefly explains how a modern sewage treatment plant works
Title from title screen
Keywords: Drainage, House; Plumbing